Physiological and biochemical changes during fruit growth, maturity and ripening of guava: a review - V, Phani Deepthi (Journal of Postharvest Technology, 2024)
Ripening is one of the most important processes in fruits, which involve changes in colour, flavour and texture, and thereby making them most  acceptable for edible purposes. A large number of physiological, biochemical and structural changes occur during ripening of fruits which  include degradation of starch or other storage polysaccharides, production of sugars, synthesis of pigments, volatile compounds and partial  solubilization of cell wall. Such obvious changes generally occur in a coordinated fashion. An understanding of these changes during ripening  is of prime importance in checking post harvest losses for developing technologies in enhancing the shelf life of fruits. In climacteric fruits,  these changes take place over a relatively short period of time and guava (Psidium guajava L.) being a climacteric fruit, exhibits a typical  increase in respiration and ethylene production during ripening. It softens readily and, therefore has a very short shelf life, which in turn makes  transportation and storage difficult. Skin colour is the best maturity index in guava as it could be monitored non-destructively during fruit  ripening and storage. Fruits attaining maturity show signs of changing colour from pale green to yellowish green. If the fruit is to be shipped to  distant markets it should be mature, full sized and of firm texture, but without an obvious colour-break on the surface. Fruits for local market  can be harvested in a more advanced stage of maturity. However, harvesting fruits at appropriate stage of maturity is critical in maintaining the  post harvest quality of guava fruits. This article takes a broad look at fruit growth, maturity, post harvest physiology and ripening of guava fruit  and the available literature is reviewed under the following heads.
Keywords: Guava; maturity; ripening,; harvest; climacteric; skin colour